Penguatan Aspek-Aspek Nature of Science and Technology dalam Pembelajaran bagi MGMP IPA Kabupaten Kaur Provinsi Bengkulu - Euis Nursaadah; Agus Sundaryono; Bhakti Karyadi (WARTA LPM, 2021)
Teaching the concept of science according to nature is important and will work well if the teacher has an understanding of the nature of science. The IPA MGMP in Kaur District facilitates teachers to upgrade their knowledge and skills to improve the learning process. The topics discussed included: 1) discussing questions on the National Examination and National Science Olympiad, 2) making parameters for the Final and Middle Examination questions 3) Classroom Action Research, and 4) learning models. No one has yet discussed how to teach science in accordance with the aspects of nature of science and technology (NOST). The purpose of this training is to improve understanding of NOST aspects which consists of 4 steps: 1) equalizing perceptions of the importance of NOST, 2) Analyzing aspects of NOST 3) and increasing teacher understanding of aspects of NOST in learning. This training was conducted for 50 teachers in Kaur District through the ICARE method (Introduction, Connection, Application, Reflection and Extend). Program evaluation is carried out by adopting the CIPP design (Context, Input, Process and Product). The results show that teachers already think that science is not just a concept of chemistry, physics, and biology. In addition, the teacher's view of scientific research is not only limited to proving concepts but also involves new findings that support technological development.